2013
DOI: 10.1080/00071668.2013.849795
|View full text |Cite
|
Sign up to set email alerts
|

An update on approaches to controlling coccidia in poultry using botanical extracts

Abstract: 1. This paper reviews the use of botanical extracts in the control of coccidial infection in poultry. 2. Some plants and their respective volatile oils and extracts have the potential to alleviate coccidiosis and reduce its severity. 3. Most plant bioactives improve some, but not all, aspects of coccidiosis with variable effectiveness against different species of Eimeria. 4. Difficulties in comparing research findings have arisen from the use of different experimental models, different active components and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 102 publications
1
51
0
2
Order By: Relevance
“…It is generally accepted that essential oils are slightly more active against Gram-positive than Gram-negative bacteria (Brenes and Roura, 2010). Comparable in vivo studies also found inhibiting effects of essential oils against pathogens such as C. perfringens, E. coli or Eimeria species (Bozkurt et al, 2013). The control of pathogenic load may also contribute to healthy microbial metabolites, improved intestinal integrity and protection against enteric disease (Bozkurt et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is generally accepted that essential oils are slightly more active against Gram-positive than Gram-negative bacteria (Brenes and Roura, 2010). Comparable in vivo studies also found inhibiting effects of essential oils against pathogens such as C. perfringens, E. coli or Eimeria species (Bozkurt et al, 2013). The control of pathogenic load may also contribute to healthy microbial metabolites, improved intestinal integrity and protection against enteric disease (Bozkurt et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Comparable in vivo studies also found inhibiting effects of essential oils against pathogens such as C. perfringens, E. coli or Eimeria species (Bozkurt et al, 2013). The control of pathogenic load may also contribute to healthy microbial metabolites, improved intestinal integrity and protection against enteric disease (Bozkurt et al, 2013). Attention should also be paid to the potential negative effects induced by essential oils on healthy intestinal bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, growth inhibition of gram-negative bacteria occurred mostly without cell integrity loss (Thapa et al, 2012). Comparable in vivo studies found inhibiting effects against pathogens such as Clostridium perfringens, E. coli and Eimeria species (Bozkurt et al, 2013). The controlled pathogen load contributed to healthy microbial metabolites, improved intestinal integrity and protection against enteric disease (Bozkurt et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Comparable in vivo studies found inhibiting effects against pathogens such as Clostridium perfringens, E. coli and Eimeria species (Bozkurt et al, 2013). The controlled pathogen load contributed to healthy microbial metabolites, improved intestinal integrity and protection against enteric disease (Bozkurt et al, 2013). Attention should be paid to the potential negative effects induced by essential oils on healthy intestinal bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The main active substances of botanicals are considered to be the plant secondary metabolites. Botanicals vary greatly due to the enormous variety of different plants used, the different methods used in their preparation, and their formulations (Christaki et al, 2012;Bozkurt et al, 2013).…”
Section: Botanicalsmentioning
confidence: 99%